Access-Site Complications in Mechanical Thrombectomy for Acute Ischemic Stroke: A Review of Prospective Trials - Shapiro, S.Z. (AJNR Am J Neuroradiol, 2020)
BACKGROUND: A shift has occurred in interventional cardiology from transfemoral to transradial access due to a 70%–80% decrease in complications. This shift has not yet taken place in other interventional specialties, perhaps owing to the lack of generalizability of findings in the cardiology data. PURPOSE: Our aim was to assess data from the recent mechanical thrombectomy prospective trials to better understand the access-site complication rate. DATA SOURCES: Articles were systematically sourced from the National Center for Biotechnology Information PubMed archive. STUDY SELECTION: According to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, prospective, randomized controlled trials published after 2008 with mention of major and/or minor femoral access-site complications in neuroendovascular mechanical thrombectomies were included. DATA ANALYSIS: Major and minor femoral access-site complications were extracted. A total complication rate was calculated with major access-site complications alone and combined with minor access-site complications. DATA SYNTHESIS: Seven prospective studies of 339 total screened met the inclusion criteria. Eleven major access-site complications were identified in of 660 total interventions, revealing a major access-site complication rate of 1.67% for patients undergoing mechanical thrombectomy with transfemoral access. If minor access-site complications were included, 35 total incidents were detected in 763 interventions, resulting in a total complication rate of 4.59%. LIMITATIONS: Multiple unspecified vessel and procedure-related complications were mentioned in the studies. CONCLUSIONS: The overall rate of major access-site complications was 1.67% in this review, which is not low and poses a risk to patients. We suggest further investigation into the feasibility and complication rates of alternative access sites for neurointerventional procedures.